An Optimal Power Allocation Scheme in Downlink Multi-user NOMA Beamforming System with Imperfect CSI - Liu, Xiaoguang; Zhang, Jun; Cai, Shu (2018 IEEE International Conference on Communication Systems (ICCS), 2018)
In this paper, we consider downlink multi-user non-orthogonal multiple access beamforming system with imperfect channel state information. In this system, we employ regularized zero-forcing precoding to reduce inter-cluster interference since it has a good performance-complexity balance. By maximizing the total capacity of the system, under the premise of ensuring users' fairness, we propose an optimal power allocation scheme. Finally, we confirm the effectiveness of the proposed scheme by simulation results. It shows that the proposed scheme can increase the cell-edge users' capacity and maintain the fairness of users.